Association of anorectal malformation with anal and rectal duplication - Karla A. Santos-Jasso; Esperanza Vidales-Nieto (Instituto Nacional de Pediatría, 2014)
The objective of this paper is to report our experience in the diagnosis and therapy of rectal and anal duplications, all associated to anorectal malformation. We present three cases of rectal duplications with anorectal malforma- tion with recto-perineal fistula and colonic duplication. Two of them with delayed diagnosis and bowel obstruction, treated with laparotomy, colostomy and side-to-side anastomosis of the proximal colonic duplica- tion; in the third case the diagnosis of the colonic and rectal duplication was made during a colostomy opening. For definitive correction, the three patients underwent abdomino-perineal approach and side-to-side anastomosis of the rectal duplication, placement of the rectum within the muscle complex, and later on colostomy closure. In a fourth patient with anorectal malformation and colostomy after birth, the perineal electro-stimulation showed two muscle complexes. A posterior sagittal approach in both showed two separate blind rectal pouches; an end- to-side anastomosis of the dilated rectum was made, and the muscle complex with stronger contraction was used for the anoplasty. The posterior sagittal approach is the best surgical option to preserve the muscle complex, with a better prognosis for rectal continence.